2005
DOI: 10.1080/00365520510012235
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic biopsies in Ussing chambers evaluated for studies of macromolecular permeability in the human colon

Abstract: Endoscopic biopsies of human colon are viable in Ussing chambers and are reliable tools for studies of mucosal permeability to protein antigens. The technique offers a broad potential for studies of mucosal function in the pathophysiology of human gastrointestinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 27 publications
(24 reference statements)
6
89
0
Order By: Relevance
“…On the other hand, the conductance was lower in surgical specimens compared to biopsies in both tissue types, Po0.001. This is in line with previous results from human colon 26 and probably refers to the thicker subepithelial layer in surgical specimens, giving higher total resistance recordings. However, it could also refer to differences in the mounting process with the influence of stretching the epithelium in surgical specimens and a higher risk of edge damage in biopsy chambers.…”
Section: Equal Permeability In Surgical Specimens and Biopsiessupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the conductance was lower in surgical specimens compared to biopsies in both tissue types, Po0.001. This is in line with previous results from human colon 26 and probably refers to the thicker subepithelial layer in surgical specimens, giving higher total resistance recordings. However, it could also refer to differences in the mounting process with the influence of stretching the epithelium in surgical specimens and a higher risk of edge damage in biopsy chambers.…”
Section: Equal Permeability In Surgical Specimens and Biopsiessupporting
confidence: 82%
“…Our group previously showed that permeability was equal in surgical specimens and biopsies of human colon 26 and initially we wanted to confirm these findings in human ileal mucosa. After 40 min of equilibration, PD was stable in all tissues.…”
Section: Equal Permeability In Surgical Specimens and Biopsiesmentioning
confidence: 94%
“…Modified 3ml Ussing chambers (Mussler Scientific Instruments, Aachen, Germany) were used to mount biopsies as described previously [14]. …”
Section: Ussing Chamber Experimentsmentioning
confidence: 99%
“…Similarly, the excised ileal human tissue maintained viability during the experiment as confirmed by a starting PD of at least À0.2 mV and a PD that remained at a level of 475% of initial value. 35,37 Thus, neither the bacteria nor the nanoparticles affected the integrity of the cell monolayers or the tissue.…”
Section: Cell Monolayer and Tissue Integritymentioning
confidence: 99%
“…Transmucosal potential difference (PD), short circuit current and electrical resistance were assessed using two pairs of electrodes (Ag/AgCl with agar-salt bridges and platinum electrodes, respectively) for assessment of tissue viability as previously described. 33,35 Before transport experiments chambers were equilibrated for 20 min to achieve steady-state conditions in PD. Live Y. pseudotuberculosis (inv þ or invÀ) were added to the mucosal side at a final concentration of 1 Â 10 8 CFU/ml.…”
Section: Confocal Microscopy Studiesmentioning
confidence: 99%